A248 INDICATIONS FOR COLONOSCOPY PRE- AND POST-COLON SCREENING PROGRAM AT ST. PAUL'S HOSPITAL. (1st March 2018) - Pi, S; Nap-Hill, E; Enns, R A; Telford, J J
Abstract: Background: Colorectal cancer (CRC) is a commonly diagnosed cancer with a lifetime prevalence of 4.5%. The removal of adenomas as well as the detection and resection of early CRC have been shown to reduce the incidence and mortality of CRC. The Canadian Task Force on Preventative Health Care recommends utilizing fecal occult blood testing (FOBT) or fecal immunochemical testing (FIT) every 2 years in men and women between the ages of 50–74. In addition, the routine use of colonoscopy for CRC screening is not recommended. In November 2013, the Colon Screening Program (CSP) was implemented with the goal of standardizing British Columbia's CRC screening strategy. Prior to this, no provincial strategy existed and significant variation existed with regards to the indication for colonoscopy. Aims: The purpose of this study is to investigate how the implementation of the CSP in BC has changed the indications for colonoscopy amongst newly diagnosed patients with colorectal cancer. Methods: A retrospective chart review of all CRC diagnosed at St. Paul's Hospital from 2010–2015 was conducted. The list of all CRC was obtained through the St. Paul's Hospital Department of Pathology after ethics approval. Results: After the implementation of the CSP, a lesser proportion of patients were diagnosed with CRC via symptoms (42% vs 57%, p=0.002) or primary colonoscopy (0.6% vs 4%, p=0.038). A greater proportion of patients were diagnosed via positive FIT + FOBT (48% vs 34%, p<0.001) and surveillance colonoscopy (6% vs 3%, p=0.03). In addition, a greater proportion were diagnosed by FIT (47% vs. 22%, p<0.001) and a lesser proportion diagnosed by FOBT (1% vs 11%, p<0.001) when compared to pre-CSP era. Conclusions: Implementation of the CSP has led to a greater proportion of colorectal cancers being diagnosed by FIT screening and surveillance colonoscopy as well as an overall reduction in colorectal cancer being diagnosed via symptoms or primary colonoscopy. The data also suggests that family physicians in BC are almost universally favouring FIT testing over the guaiac based FOBT. These results support that the CSP has been successful in aligning the indications for colonoscopy with the recommendations made by the Canadian Task Force on Preventative Health Care. Funding Agencies: St. Paul's Hospital GI Research Institute